Quantitative evaluation of the adhesion of bioactive glasses onto Ti6Al4V substrates. (5th May 2016) - Matinmanesh, A.; Rodriguez, O.; Towler, M.R.; Zalzal, P.; Schemitsch, E.H.; Papini, M.
Abstract: This paper presents a new method for applying a uniform thickness bioactive glass coating to a Ti6Al4V substrate and postulates a fracture mechanics testing methodology to quantify the glass/metal adhesion in terms of a measured critical strain energy release rate ( G IC ). Bi-layer double cantilever beam (DCB) test specimens were developed for this purpose and were found to generate repeatable and consistent measures of G IC for the tested system. The measured G IC of the coating decreased significantly from 6.2 to 2.5 J/m 2 with an increase in coating thickness from 90 to 390 μm. Since high temperature enamelling processes can potentially introduce significant residual stresses in the glass/metal system, the residual stresses were measured and their impact on the adhesion was assessed. Increases in the coating thickness were found to increase the residual stresses from 6.8 to 17.9 MPa, thus decreasing the adhesion between the glass and the Ti alloy. Finally, the directional stability of the crack within the coating was quantified by calculating the T -stress for coatings with different thicknesses and it was found that as the coating thickness increased, the crack destabilized and tended to kink rather than travel in a straight line. Graphical abstract: Highlights: A new method for applying a uniform thickness bioactive glass coating to a Ti6Al4V substrate was developed. A novel methodology for quantifying the adhesive strength of enamelled bioactive glass coatings was presented. Thinner glass coatings proved to have higher resistance against fracture than thicker ones. Residual stresses in the glass/metal system were measured and it was found that they increase with the coating thickness. It was found that as the coating thickness increased, the crack destabilized.